Sandinism and Polítical Pragmatism. Militants Generations in Nicaragua 1979-2016 (Palimpsesto, 2017)
Politics in Nicaragua have undergone abrupt changes over the last four decades. The Sandinista National Liberation Front (FSLN) began a revolution through a guerrilla struggle, it faced an internal war during its ten years in power which divided the country between Sandinistas and Counterrevolutionaries, and finally in 1990 it was ousted from power in a 1990 election. These rapid political changes in politics led the FSLN to return to power in 2006 after 16 years of conservative rule. This article will explore the evolution of Sandinista militancy, analyse some of the continuity and breaks among militants and look at the shifts in party policies and positions inÂ recent years through a series of interviews with former FSLN guerrilla who were demobilized between 1990 and 1993.
Keywords: Militancy; Sandinismo; Party Practices; Speech.